Hydrogeochemistry of shallow aquifer Manukan Island, Sabah - Lin, Chin Yik (2011)
A total of 180 shallow groundwater samples in Manukan island’s aquifer were collected for major and trace elements analysis in order to obtain a general understanding of the hydrogeochemistry in the study area. Groundwater and soil samples were collected in the low elevation area of the island to evaluate the general chemical composition of groundwater and soil, hydrogeochemical facies in the natural shallow aquifer as well as the mineralogy of the soil in the aquifer. A total of 10 boreholes were installed perpendicularly from the shoreline towards inland of the island. Different layer (O, A, E, B and C zone) of soil samples were collected from the soil core during coring process. For water samples analysis, in situ readings were recorded in the field. Chemical parameters such as chloride (Cl-), bicarbonate (HCO3-), calcium (Ca2+), magnesium (Mg2+), sodium (Na+) and potassium (K+) were analysed in the laboratory. For mineralogy analysis, soil samples were pulverized and sieved prior to X-ray diffraction (XRD) and X-ray Florescence (XRF) analysis. Visual verification of these minerals were obtained from the images captured by scanning electron microscopy (SEM). Measurements of the soil’s loss on ignition (L.O.I.) and total metals in the soil samples were also included in the results, respectively. The results indicate that the groundwater collected from the boreholes were moderately mineralized with EC ranged from 460 μS/cm to 3400 μS/cm. The previous indiscriminate pumping activities had led to seawater intrusion into the aquifer. This study shows that the groundwater were generally classified as Ca-HCO3, CaCl2, NaHCO3 and NaCl water type as illustrated in the Piper diagrams. This study also found that the PHREEQC calculations were in agreement with the soil geochemical composition data. The PHREEQC calculations for calcite, aragonite and dolomite solubility revealed positive values in the saturation indices (SI), indicating supersaturated state i.e. precipitation shall occur with respect to these minerals. The baseline geochemical results clearly revealed that the major chemical composition of the soil in the study area was mainly composed of quartz, calcite, aragonite as well as magnesium calcite. XRF analysis depicts a general trend where the soil chemical composition varies significantly with depth and distance from shore. The composition of calcium oxides increases with depth. Conversely, silicon oxide showed a decreasing trend in composition with increasing depth which dominated by carbonates minerals. SEM images visually showed the presence of quartz, calcite and aragonite minerals in the soil samples and further supports the data obtained from XRD.